2019
DOI: 10.1523/jneurosci.0428-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Predictability and Uncertainty in the Pleasure of Music: A Reward for Learning?

Abstract: Music ranks among the greatest human pleasures. It consistently engages the reward system, and converging evidence implies it exploits predictions to do so. Both prediction confirmations and errors are essential for understanding one's environment, and music offers many of each as it manipulates interacting patterns across multiple timescales. Learning models suggest that a balance of these outcomes (i.e., intermediate complexity) optimizes the reduction of uncertainty to rewarding and pleasurable effect. Yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
132
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(171 citation statements)
references
References 67 publications
10
132
4
3
Order By: Relevance
“…This result documents the independence of structural and veridical predictability, and it contrasts with earlier findings in which stimulus repetition was positively correlated with likability (Johnston, 2016). Data from both experiments by Gold et al (2019a) also showed stronger Wundt effects (i.e., higher skewness and kurtosis values) in participants with higher musical perceptual abilities. Behaviorally, this equates to sharper musical preferences, but interestingly not to a general preference shift toward more complex music in musical experts.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…This result documents the independence of structural and veridical predictability, and it contrasts with earlier findings in which stimulus repetition was positively correlated with likability (Johnston, 2016). Data from both experiments by Gold et al (2019a) also showed stronger Wundt effects (i.e., higher skewness and kurtosis values) in participants with higher musical perceptual abilities. Behaviorally, this equates to sharper musical preferences, but interestingly not to a general preference shift toward more complex music in musical experts.…”
contrasting
confidence: 51%
“…To reliably measure musical complexity, a recent article published in The Journal of Neuroscience used a computational model of auditory processing that acquires the syntactic structure (i.e., melodics) of a given musical style through variable-order Markov modeling (Gold et al, 2019a). The model predicts the pitch and onset time of a subsequent note based on long-and short-term musical contexts, weighed by their relative certainty.…”
mentioning
confidence: 99%
“…Notably, bodily reactions such as 'chills' which are generally associated with particularly intense and pleasurable responses to music, and have been associated with greater engagement of the NAcc (Grewe et al, 2009(Grewe et al, , 2005Mas-Herrero et al, 2018b;Salimpoor et al, 2009), are often experienced following musical surprises (Grewe et al, 2007;Guhn et al, 2007;Harrison and Loui, 2014;Nagel et al, 2008;Panksepp, 1995;Sloboda, 1992). Finally, recent studies using an information-theoretic model of auditory expectation indicate that listeners may prefer music containing surprises, yet in a context in which those can be learned and anticipated (Cheung et al, 2019;Gold et al, 2019b). These findings resonate with learning theories that suggest that the information gain of balancing uncertainty and surprise (Oudeyer et al, 2016) could be intrinsically rewarded by the brain in order to foster our fundamental need of generating accurate models of the world.…”
Section: The Striatummentioning
confidence: 99%
“…food). For instance, while hedonic reactions and preference for primary tastes, such as sweetness, are largely innate and highly preserved across species and individuals (Berridge, 2000), musical preferences are shaped by previous exposure, cognitive abilities, musical education, and cultural background; thus they are largely influenced by learning and plasticity (Gold et al, 2019b(Gold et al, , 2019aGreenberg et al, 2015;Haumann et al, 2018). In this regard, recent models hold that music-induced pleasure may be driven by anticipation and prediction mechanisms, which, in turn, have been linked to predictive coding theories (Cheung et al, 2019;Gold et al, 2019b;Koelsch et al, 2019;Salimpoor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation